A Study on GSM and GPRS Architecture and Design - Dukitha, M; surya, G. Jai (International Journal of Computer Sciences and Engineering, 2025)
The General Packet Radio System (GPRS) is a new service that provides actual packet radio access for mobile Global System for Mobile Communications (GSM) and time-division multiple access (TDMA) users In addition, GPRS will allow improved quality of data services as measured in terms of reliability, response time, and features supported The main benefits of GPRS are that it reserves radio resources only there's information to send and it reduces reliance on ancient circuit-switched network components. GPRS stands out mutually major development within the GSM normal that edges from packet switched techniques to supply mobile subscribers with the abundant required high bit rates for bursty data transmissions. It is potential on paper for GPRS subscribers to use many time slots (packet information channels) at the same time reaching a touch rate of concerning 170kbit/s. Volume-based charging is possible because channels are allocated to users only when packets are to be sent or received. Bursty knowledge applications create it attainable to balance a lot of expeditiously the network resources between users as a result of the supplier will use transmission gaps for different subscriber activities.